Understanding the economic burden of cancer care and the utility of health insurance: An exploratory cross-sectional study in a tertiary care hospital in Karnataka, India - G Somu; Annu Mathew; R Vani Lakshmi (Wolters Kluwer Medknow Publications, 2023)
Background: Families and caregivers of cancer patients experience significant financial challenges associated with out-of-pocket (OOP) expenditures. Objectives: This study aims to assess the OOP expenditure and its impact on the livelihood of patients and families, associated with receiving cancer care from a teaching hospital in Karnataka. Materials and Methods: It focuses on understanding health insurance use and its effects on OOP expenses for cancer care based on data obtained from 271 patients receiving treatment for more than 6 months. A structured questionnaire was developed and used for data collection and focused on obtaining direct costs such as consultation fees, surgery costs, and radiotherapy costs and indirect costs such as travel expenses, food costs, and patient income loss, as well as questions that measure the impact of the financial burden on patients and their associated livelihood. Results: In the present study, the median cost of OOP expense incurred for cancer treatment is estimated to be 3.10 lakh Indian rupees. It was also found that patients enrolled in public health insurance schemes, especially Ayushman Bharath-Arogya Karnataka have lesser OOP expenditure than those with either private health insurance or no health insurance. Conclusions: This indicates the need for effective implementation of various public health insurance schemes and their ability to protect patients from huge OOP expenses and related financial risks.